2018
DOI: 10.1001/jamaoncol.2017.3501
|View full text |Cite
|
Sign up to set email alerts
|

Consolidative Radiotherapy for Limited Metastatic Non–Small-Cell Lung Cancer

Abstract: clinicaltrials.gov Identifier: NCT02045446.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
460
1
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 864 publications
(475 citation statements)
references
References 51 publications
9
460
1
5
Order By: Relevance
“…In addition to surgical resection, SBRT has been shown to be effective, demonstrating high rates of local control and improved PFS in prospective studies. 34,35 In a randomized phase II study of patients with oligometastases from mixed histologies (SABR-COMET), Palma et al reported improved outcomes in PFS (12 vs. 6 months, p < 0.001) and OS (41 vs. 27 months, p = 0.09) with the addition of SBRT to standard of care systemic therapy compared to systemic therapy alone. 36 Although phase III studies are needed, the data supporting an increased role for local therapies in oligometastatic disease are encouraging, particularly if advances in systemic therapies for patients with HCC, such as immunotherapies, continue to evolve.…”
Section: Stereotactic Body Radiation Therapy For Extrahepatic Lesionsmentioning
confidence: 99%
“…In addition to surgical resection, SBRT has been shown to be effective, demonstrating high rates of local control and improved PFS in prospective studies. 34,35 In a randomized phase II study of patients with oligometastases from mixed histologies (SABR-COMET), Palma et al reported improved outcomes in PFS (12 vs. 6 months, p < 0.001) and OS (41 vs. 27 months, p = 0.09) with the addition of SBRT to standard of care systemic therapy compared to systemic therapy alone. 36 Although phase III studies are needed, the data supporting an increased role for local therapies in oligometastatic disease are encouraging, particularly if advances in systemic therapies for patients with HCC, such as immunotherapies, continue to evolve.…”
Section: Stereotactic Body Radiation Therapy For Extrahepatic Lesionsmentioning
confidence: 99%
“…An increasing body of literature is now supporting the use of local ablative approaches with curative intent in oligometastatic patients, the most convincing data arising from the group of NSCLC patients [11,25,26]. Nevertheless, in clinical situations such as the occurrence of ultra-central lung oligometastases, the delivery of SBRT to radical doses can be technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that RT provided significantly better PFS and OS, relative to historical values for patients who had received only systemic treatment. A later prospective study (Iyengar et al 2018) involved 29 patients with oligometastatic stage IV NSCLC, including 14 patients who were treated using stereotactic ablative radiotherapy (SAbR) plus maintenance chemotherapy and 15 patients who were treated using maintenance chemotherapy. That trial was closed early after an interim analysis revealed that SAbR plus maintenance chemotherapy yielded significantly improved PFS (9.7 months vs. 3.5 months, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing awareness regarding the concept of oligometastasis, which, relative to extensive metastasis, is thought to involve a milder stage of tumor invasion, with fewer metastases (≤ 3-5 metastases) and localization (Ashworth et al 2013;De Rose et al 2016;Mitchell et al 2019). Multiple studies have shown that patients with stage IV non-small cell lung cancer (NSCLC) generally experience progression of advanced disease at the original sites of gross disease and that patients with oligometastasis may potentially be cured via local treatment (Iyengar et al 2018). Thus, local consolidation therapy (LCT) involving surgery and radiotherapy (RT) is expected to prolong the survival of patients with oligometastatic NSCLC.…”
Section: Introductionmentioning
confidence: 99%